Novel relationships between porcine fetal size, sex, and endometrial angiogenesis†. Issue 1 (23rd April 2019) - Stenhouse, Claire; Hogg, Charis O; Ashworth, Cheryl J
Abstract: It is hypothesized that growth restriction occurs due to inadequate vascularization of the feto-maternal interface. Evidence exists for sexual dimorphism in placental function although associations between fetal sex and the endometrium remain poorly investigated. This study investigated the relationship between porcine fetal size, sex and endometrial angiogenesis at multiple gestational days (GD). Endometrial samples supplying the lightest and closest to mean litter weight (CTMLW), male and female Large White X Landrace conceptuses or fetuses were obtained at GD18, 30, 45, 60, and 90 (n = 5–9 litters/GD). Immunohistochemistry for CD31 revealed a greater number of blood vessels in endometrium supplying females compared to those supplying males at GD45. Endometrial samples supplying the lightest fetuses had fewer blood vessels (GD60) and uterine glands (GD90) compared to those supplying the CTMLW fetuses. Quantitative PCR revealed decreased CD31 (GD60), HPSE and VEGFA (GD90) expression, alongside increased HIF1A (GD45) expression in endometrial samples supplying the lightest compared to the CTMLW fetuses. At GD30, PTGFR, CD31, and VEGFA mRNA expression was increased in samples supplying female fetuses compared to those supplying male fetuses. Intriguingly, decreased expression of ACP5, CD31, HIF1A, and VEGFA mRNAs was observed at GD60 in endometrial samples supplying female fetuses compared to those supplying their male littermates. Endothelial cell branching assays demonstrated impaired endothelial cell branching in response to conditioned media from endometrial samples supplying the lightest and female fetuses compared with the CTMLW and male fetuses, respectively. This study has highlighted that endometrial tissues supplying the lightest and female fetuses have impaired angiogenesis when compared with the CTMLW and female fetuses respectively. Importantly, the relationship between fetal size, sex and endometrial vascularity is dynamic and dependent upon the GD investigated. Abstract : Endometrium supplying the lightest and female fetuses has impaired angiogenesis compared to which supplying normally-grown and female littermates, respectively. The relationship between fetal size, sex and endometrial vascularity depends upon the gestational day investigated.